Cosmopolitan Species As Models for Ecophysiological Responses to Global Change: The Common Reed Phragmites australis - Eller, Franziska; Skálová, Hana; Caplan, Joshua S.; Bhattarai, Ganesh P.; Burger, Melissa K.; Cronin, James T.; Guo, Wen-Yong; Guo, Xiao; Hazelton, Eric L. G.; Kettenring, Karin M.; Lambertini, Carla; McCormick, Melissa K.; et al. (Frontiers in Plant Science, 2017)
Phragmites australis is a cosmopolitan grass and often the dominant species in the ecosystems it inhabits. Due to high intraspecific diversity and phenotypic plasticity, P. australis has an extensive ecological amplitude and a great capacity to acclimate to adverse environmental conditions; it can therefore offer valuable insights into plant responses to global change. Here we review the ecology and ecophysiology of prominent P. australis lineages and their responses to multiple forms of global change. Key findings of our review are that: (1) P. australis lineages are well adapted to regions of their phylogeographic origin and therefore respond differently to changes in climatic conditions such as temperature or atmospheric CO2; (2) each lineage consists of populations that may occur in geographically different habitats and contain multiple genotypes; (3) the phenotypic plasticity of functional and fitness-related traits of a genotype determine the responses to global change factors; (4) genotypes with high plasticity to environmental drivers may acclimate or even vastly expand their ranges, whereas genotypes of medium must acclimate or experience range-shifts, and those with low plasticity may face local extinction; (5) responses to ancillary types of global change, like shifting levels of soil salinity, flooding, and drought, are not consistent within lineages and depend on adaptation of individual genotypes. These patterns suggest that the diverse lineages of P. australis will undergo intense selective pressure in the face of global change such that the distributions and interactions of co-occurring lineages, as well as those of genotypes within-lineages, are very likely to be altered. We propose that the strong latitudinal clines within and between P. australis lineages can be a useful tool for predicting plant responses to climate change in general and present a conceptual framework for using P. australis lineages to predict plant responses to global change and its consequences.